2021
DOI: 10.1021/acsami.1c01659
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-Substituted Lithium/Sodium closo-Decaborates: Syntheses, Characterization, and Solid-State Ionic Conductivity

Abstract: Solid-state electrolytes based on closo-decaborates have caught increasing interest owing to the impressive room-temperature ionic conductivity, remarkable thermal/chemical stability, and excellent deformability. In order to develop new solid-state ion conductors, we investigated the influence of iodine substitution on the thermal, structural, and ionic conduction properties of closo-decaborates. A series of iodinated closo-decaborates, M2[B10H10–n I n ] (M = Li, Na; n = 1, 2, 10), were synthesized and charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…The large and highly symmetrical borate cages allow for thermally induced orientational disorder that is key to high ionic conductivities, as the transition to a sublattice of rotationally fluidic anions facilitates liquid-like interstitial cation diffusion . A range of novel metal hydrides have recently demonstrated exceptionally high ionic conductivity and large electrochemical stabilities also toward metallic anodes, such as Li, Na, Mg, or Ca, which inspire development of batteries far beyond the commercial lithium battery. …”
Section: Introductionmentioning
confidence: 99%
“…The large and highly symmetrical borate cages allow for thermally induced orientational disorder that is key to high ionic conductivities, as the transition to a sublattice of rotationally fluidic anions facilitates liquid-like interstitial cation diffusion . A range of novel metal hydrides have recently demonstrated exceptionally high ionic conductivity and large electrochemical stabilities also toward metallic anodes, such as Li, Na, Mg, or Ca, which inspire development of batteries far beyond the commercial lithium battery. …”
Section: Introductionmentioning
confidence: 99%
“…A series of NMR, QENS, and MD calculations have demonstrated that the cation translational mobility is correlated with the reorientation rate of the LBRA consistent with a "paddle-wheel" mechanism [10,25,27,28]. This cation translational motion and anion reorientation rate can be tuned via temperature (phase transitions), cation vacancies, the type of atom attached to the boron cage (i.e., H, Cl, F, Br), and LBRA size [7,12,13,[29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 85%
“…Halogenation of the closo‐decaborate anion has been extensively studied due to the importance and versatility of halo‐decaborate derivatives though most of which found it exceedingly difficult to get a selective reaction that leads only to a mono‐substituted derivative [21b,46] . In fact, direct halogenation of closo‐decaborate with dihalogens (chlorine, bromine, iodine) and recently with HCl yields a mixture of derivatives with uncontrolled degrees of substitution [B 10 H 10‐y X y ] 2− [21c,47] .…”
Section: Substitution Derivatives In Closo‐derivatives Of [B10h10]2−mentioning
confidence: 99%